(untitled) (Research, Society and Development, 2020)
The objective of this study was to identify genotypes of V. unguiculata under salt stress conditions that present less infestation by Aphis craccivora and greater productivity. The experiment was carried out in the experimental area of Fazenda Alvorada, (08º22’28 ”South, 43º51’34” West, 229 m altitude), in two harvests 2017 and 2018. Planting took place in August and harvesting in November. The plots were constituted by levels of electrical conductivity (CE) 0.5; 1.75; 3.0; 4.25 and 5.50 dS m-1, and the subplots composed of the genotypes: BRS Tumucumaque, BRS Guariba and BRS Imponente. The experimental design was in randomized blocks and subdivided plots, with four replications. The occurrence of A. craccivora differed in the two harvests. In the first harvest, 2017, the greatest abundance of aphids was recorded in the area, 27.15% of the plants sampled during the entire evaluation period were infested by the aphid. The BRS Guariba genotype showed the least infestation by A. craccivora and the highest productivity. The increase in the electrical conductivity of the irrigation solution reduced the leaf area and the amount of dry mass of the aerial part of the bean genotypes, in both crops. According to the trail analysis, the occurrence of A. craccivora has a direct and positive correlation with the dry mass variable and a negative correlation with the leaf area variable. Under the studied conditions, there was no effect of salt stress on the occurrence and population dynamics of A. craccivora.